(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Introduction: Controversy exits about the optimal time when to clamp the umbilical cord after the birth of the baby. The most important points of difference relate to maternal and infant safety. In most of the countries, majority of obstetricians and midwives clamp umbilical cord immediately after birth. In poorly resource areas immediate clamping of umbilical cord deprived the infant from increasing its iron stores which are enhancing free of cost. This study was designed to see the effect of early and delayed clamping on neonatal anemia. Objectives: This study was designed to compare the neonatal anemia in early and delayed cord clamping in term babies. Methodology: Randomized controlled trial was carried out over a period of six months from 1-72013 to 31-12-2013 at Department of Obstetrics and Gynaecology Lady willingdon Hospital Lahore. 420 cases were admitted in the labour ward, fulfilling the including criteria were included in the study. After taking the informed consent patients were divided in two equal groups randomly by using random number table. Haematocrit was noted of infants six hours after birth having early cord clamping within 15 seconds and late cord clamping at one minute after the birth. Results: In group A (early clamping) the average age of the mothers was 27.45+ 3.8 years with age range of 20 years (20-40) years. In group B (delayed clamping) the mean age of mothers was 27.9+ 4.2 years with age range 20 years of age (21-40) years. In group A the average gestational age was 38.80 ± 0.65 weeks with gestational amenorrhea range 2 weeks (38-40) weeks. In group B the mean gestational amenorrhea was 38.79 + 0.65 weeks with gestational amenorrhea range 2 weeks (38-40) weeks. As long as neonatal anemia was concerned, in early cord clamping group 35 (16.7%) babies had Haematocrit < 45% and in delayed cord clamping group only 13 (6.2%) of the babies had Haematocrit < 45% using chisquare statistical test, the frequency of Haematocrit < 45% was highly significantly less in delayed cord clamping group as compared to early cord clamping group, i.e. p-value= 0.001. Conclusion: It was concluded, that there were less chances of neonatal anemia in delayed cord clamping as compared to early cord clamping in term infants, p-value 0.001. So the delayed cord clamping should be adopted in our setup to reduce the frequency of anemia in children.